THE LANGUAGE WITHIN: MORPHOLOGICAL INSIGHTS INTO NOSHI GILANI'S POETRY - Aiman Imran; Tahir Shah; Sohail Khan; Savaira Muzammil; Gul Shumaila Taj (International Journal of Contemporary Issues in Social Sciences, 2024)
Morphology studies the way words are built and how their parts work together. It enhances our understanding of how meaning is constructed in language by joining together different units called morphemes. The study aims to categorize the different types of morphemes present in Noshi Gilani’s poetry. It further examines her poetry through the lens of Leonard Bloomfield’s concept of morphemes. His linguistic framework emphasizes the smallest unit of meaning which provides the fundamental approach for the analysis. By focusing on different types of morphemes such as free and bound morphemes and the subtypes of bound morphemes which are named as derivational and inflectional morphemes, the analysis provides the morphological insights into Noshi Gilani’s poetry. The methodology used for the study is qualitative method with descriptive approach which relies on close reading of poems. The findings highlight, the relevance of morphological analysis in understanding literary texts for further research on the intersection of linguistics and literature more specifically in context of Urdu poetry.